Analisis Penerimaan Mahasiswa Terhadap Sistem Informasi Akademik (SIAKAD) dengan Metode Technology Acceptance Model (TAM) - Librado, Dison (STMIK Palangkaraya, 2017)
Computer based data processing is expected to improve user performance, but the computer was not completely accepted by individuals. STMIK AKAKOM in one of their activities applied information technology to SIAKAD that provides some features for learning activities on campus The analysis of SIAKAD acceptance by students using the technology acceptance model (TAM), with partial least square , is to know how the behavior of SIAKAD users as the end user? It would be related to usefulness (PU), ease of use (PEOU), attitude toward using (ATU), and behavioral intention to use (BITU). From the analysis of data, the results is mention that there were a positive and significant influence between the variables. Technology acceptance factors that inflict attitude to use SIAKAD by student in their learning activities is the ease of use and usefulness )